2020
DOI: 10.3390/gels6030024
|View full text |Cite
|
Sign up to set email alerts
|

Volume Transition and Phase Coexistence in Polyelectrolyte Gels Interacting with Amphiphiles and Proteins

Abstract: Polyelectrolyte gels have the capacity to absorb large amounts of multivalent species of opposite charge from aqueous solutions of low ionic strength, and release them at elevated ionic strengths. The reversibility offers the possibility to switch between “storage” and “release” modes, useful in applications such as drug delivery. The review focuses on systems where so-called volume phase transitions (VPT) of the gel network take place upon the absorption and release of proteins and self-assembling amphiphiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 112 publications
(185 reference statements)
0
12
0
Order By: Relevance
“…We observed that the formation of collapsed shells could be avoided if the concentration of CPC solution used for loading is rather low (for instance, lower than 0.25 M for PAAm-AMPSA-4s hydrogel). Note that, in these experiments, we tried to avoid the formation of dense shells of polymer-surfactant complex, which are observed when the surface region collapses because of complex formation, whereas the central part of the gel remains in the swollen state [47][48][49][50]. Such collapsed shells release a considerable amount of CPC, so that the disinfectant is quickly exhausted, shortening the antiseptic activity of the material.…”
Section: Loading Of the Hydrogels With Disinfectantsmentioning
confidence: 99%
“…We observed that the formation of collapsed shells could be avoided if the concentration of CPC solution used for loading is rather low (for instance, lower than 0.25 M for PAAm-AMPSA-4s hydrogel). Note that, in these experiments, we tried to avoid the formation of dense shells of polymer-surfactant complex, which are observed when the surface region collapses because of complex formation, whereas the central part of the gel remains in the swollen state [47][48][49][50]. Such collapsed shells release a considerable amount of CPC, so that the disinfectant is quickly exhausted, shortening the antiseptic activity of the material.…”
Section: Loading Of the Hydrogels With Disinfectantsmentioning
confidence: 99%
“…In many applications the polyelectrolyte networks are spherical microgel particles with diameters in the range 10–1000 µm. There are a number of research papers showing that proteins and peptides can be loaded onto such microgels at low ionic strength and subsequently released at elevated ionic strengths [ 4 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The electrostatic interaction with the charged network does not seem to denature the molecules; instead the environment inside the microgel has been shown to protect them against degrading species [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic interaction with the charged network does not seem to denature the molecules; instead the environment inside the microgel has been shown to protect them against degrading species [ 34 , 35 ]. The reversible loading-release property is particularly efficient for multivalent proteins and species forming aggregates of multivalent charge, such as micelle forming surfactants [ 28 , 31 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. At low ionic strength the gain in entropy from replacing a large number of network counterions with a small number of multivalent species provides a strong driving force for binding.…”
Section: Introductionmentioning
confidence: 99%
“…Tanaka’s work has stimulated a huge interest in the theoretical and experimental studies on the volume phase transition in hydrogels [ 1 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Because the additional ionic term in eq 1 significantly affects the swelling properties, the existence of ionic groups facilitates the volume phase transition in hydrogels.…”
Section: Swelling-deswelling Transition Of Stimuli Responsive Hydrogelsmentioning
confidence: 99%
“…Many synthetic and biological hydrogels containing ionic groups exhibit a reversible discontinuous volume phase transition depending on the external stimuli such as temperature, pH, composition of the solvent, etc. [ 1 , 15 , 17 , 19 , 20 , 23 , 24 , 25 ]. Because the external stimuli affect the extent of polymer–solvent interactions, the volume phase transition occurs due to the change of the χ parameter of polymer–solvent system.…”
Section: Swelling-deswelling Transition Of Stimuli Responsive Hydrogelsmentioning
confidence: 99%